2015
DOI: 10.1007/s12549-015-0200-5
|View full text |Cite
|
Sign up to set email alerts
|

Eocene fossils and the early evolution of frogmouths (Podargiformes): further specimens of Masillapodargus and a comparison with Fluvioviridavis

Abstract: New fossils of the podargiform Masillapodargus longipes are described from the early Eocene German fossil site Messel. Previously unreported skeletal details of this species confirm its assignment to Podargiformes (frogmouths), and especially the wing and pectoral girdle bones exhibit close similarities to crown group Podargiformes. Here, I show that the postcranial skeletal morphology of Masillapodargus is quite different from that of the early Eocene North American taxon Fluvioviridavis, for which podargifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…In the case of Masillapodargus and Scaniacypselus, neither of the alternative placements for these taxa indicated by the two total-evidence analyses had obviously superior statistical support. However, the phylogenetic positions for these taxa found under molecular scaffolding were generally more congruent with the conclusions of previous studies [8,36,37,39], and tended to be characterized by greater numbers of unambiguous morphological synapomorphies compared to the results of the simultaneous combined analysis. We are, therefore, hesitant to accept the novel placements recovered for Masillapodargus, Eocypselus, and Scaniacypselus recovered by the combined molecular-morphological analysis.…”
Section: Effects Of Alternative Total-evidence Approachessupporting
confidence: 81%
See 4 more Smart Citations
“…In the case of Masillapodargus and Scaniacypselus, neither of the alternative placements for these taxa indicated by the two total-evidence analyses had obviously superior statistical support. However, the phylogenetic positions for these taxa found under molecular scaffolding were generally more congruent with the conclusions of previous studies [8,36,37,39], and tended to be characterized by greater numbers of unambiguous morphological synapomorphies compared to the results of the simultaneous combined analysis. We are, therefore, hesitant to accept the novel placements recovered for Masillapodargus, Eocypselus, and Scaniacypselus recovered by the combined molecular-morphological analysis.…”
Section: Effects Of Alternative Total-evidence Approachessupporting
confidence: 81%
“…Nesbitt et al [36] later described a second specimen of Fluvioviridavis and ran a phylogenetic analysis that recovered it as a stem-podargid, a conclusion also supported by the phylogenetic analysis of Ksepka et al [8]. However, Mayr [37] expressed scepticism of podargiform affinities for Fluvioviridavis, noting that its humerus and coracoid morphology is more similar to that of Steatornis. Mayr instead suggested that Fluvioviridavis was an early-diverging strisorean excluded from a clade including all non-steatornithiform strisoreans (Podargocypseli), a grouping not supported by the present study.…”
Section: Affinities Of Fluvioviridavismentioning
confidence: 95%
See 3 more Smart Citations